Women, religion, and the Atlantic world (1600-1800) - Vollendorf, Lisa; Kostroun, Daniella J., 1970- (UCLA Clark Memorial Library series., 2009)
"This innovative collection of essays looks at the complex interplay between religion, gender, and authority in the early modern Atlantic world. Drawing on historical, literary, and anthropological methodologies, the essays explore the significance of the 'Atlantic community' and challenge the conventional divisions of nation-bound inquiry in the humanities. The contributors focus on European, indigenous, Creole, African, and mestiza women's interactions with shifting paradigms of Protestantism, Catholicism, Judaism, and syncretic beliefs to highlight the unique cultural dynamics of the Atlantic. The volume considers these themes within the context of a wide range of individual, imperial, and institutional cases, involving such diverse figures as an African slave, a Peruvian nun, and Native American healers, who in various ways challenged and exposed the hypocrisy of patriarchal religious and political institutions. Together the contributors investigate and bring to life the early modern Atlantic world's changing cultural landscape and its impact on slaves and free people, migrants and natives, nuns, wives, widows, mothers, and singlewomen. In casting the project within the Atlantic framework, the essays seek to transcend the limitations of binaries of Old versus New World. Catholic versus Protestant, indigenous versus European. Instead the volume aims to examine the changes created by the movement of people, ideas. objects, and beliefs in the shared spaces of the Atlantic, a community connected by economic, political. and cultural ties.